Cydnidae pigmentation − dermoscopic features - BM Shashi Kumar; AS Savitha (Wolters Kluwer Medknow Publications, 2021)
Pigmented spots on the skin are caused by burrowing bugs of family Cydnidae. These are commonly seen in monsoon, and the pigmentation is due to secretion by the insect. Here we report a case of Cydnidae pigmentation with characteristic dermoscopic features. Dermoscopic features included dark brown pigmentation over the dermatoglyphics with enhanced pigmentation around the sweat pores. The pigmentation which is seen commonly over the acral areas may be mistaken for lentigines or melanoma. Identifying the classical features on dermoscopy prevents the patient from undergoing unwanted investigations.